2015
DOI: 10.1007/s11886-015-0586-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon and Stent Therapies for Endovascular Treatment of Atherosclerotic Superficial Femoral Artery Disease

Abstract: Endovascular management of superficial femoral artery disease has historically been limited to percutaneous balloon angioplasty, atherectomy, and bare-metal stents. However, these therapies have been plagued by high restenosis and target lesion revascularization rates. More recent technologies such as drug-coated stents and balloons are designed to combat restenosis by locally delivering antiproliferative drugs. Several randomized controlled trials have directly compared these antiproliferative drug-delivering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…At 6 and 12 months after operation, there was no significant difference between the two groups, suggesting that domestic paclitaxel DCB is equivalent to BMS in improving Rutherford classification and ABI index. A previous study [ 12 ] analyzed the efficacy of DCB in the treatment of elderly patients with long-segment ASO lesions and found that the short-term and midterm efficacies of DCB in the treatment of long-segment ASO lesions were not inferior to that of BMS. It was considered that DCB could rapidly release the coating drug to the intima of the diseased vessel through balloon dilatation, which not only reduced the stimulation of foreign body implantation to the wall but also avoided the risk of restenosis after BMS.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 and 12 months after operation, there was no significant difference between the two groups, suggesting that domestic paclitaxel DCB is equivalent to BMS in improving Rutherford classification and ABI index. A previous study [ 12 ] analyzed the efficacy of DCB in the treatment of elderly patients with long-segment ASO lesions and found that the short-term and midterm efficacies of DCB in the treatment of long-segment ASO lesions were not inferior to that of BMS. It was considered that DCB could rapidly release the coating drug to the intima of the diseased vessel through balloon dilatation, which not only reduced the stimulation of foreign body implantation to the wall but also avoided the risk of restenosis after BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation balloons for angioplasty and stents, which are coated with drugs to prevent early restenosis, are currently under development. [21][22][23] The efficiency of such drug-coated balloons and drug eluting stents can be investigated by directly monitoring the concentration and long-term release spectroscopically, as the active compounds also exhibit distinct spectroscopic properties. 24,25 The applied conditions of several seconds of nonfocused laser illumination at 100 mW within the artery did not lead to any noticeable alterations of the walls of the blood vessels, as confirmed by subsequent histopathological staining.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy calcification on the target lesion may reduce drug delivery to the vessel wall via DCB (7). Sub-intimal angioplasty in total occlusion and long lesions also reduces the effectiveness of DCB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mobility and length of the location of FAD facilitate the de- velopment of long stent fractures, restenosis and thrombosis after stent implantation. The most important advantages of DCB versus stents for the treatment of FAD are tied to having more homogeneous and anti-proliferative drug in high doses required per square millimeter, and no foreign substances that might trigger inflammatory processes (6,7).…”
Section: Introductionmentioning
confidence: 99%